Impact of HLA in mother and child on disease progression of pediatric human immunodeficiency virus type 1 infection. - Thobakgale, C; Prendergast, A; Crawford, H; Mkhwanazi, N; Ramduth, D; Reddy, S; Molina, C; Mncube, Z; Leslie, A; Prado, J; Chonco, F; Mphatshwe, W; et al. (2009)
A broad Gag-specific CD8(+) T-cell response is associated with effective control of adult human immunodeficiency virus (HIV) infection. The association of certain HLA class I molecules, such as HLA-B*57, -B*5801, and -B*8101, with immune control is linked to mutations within Gag epitopes presented by these alleles that allow HIV to evade the immune response but that also reduce viral replicative capacity. Transmission of such viruses containing mutations within Gag epitopes results in lower viral loads in adult recipients. In this study of pediatric infection, we tested the hypothesis that children may tend to progress relatively slowly if either they themselves possess one of the protective HLA-B alleles or the mother possesses one of these alleles, thereby transmitting a low-fitness virus to the child. We analyzed HLA type, CD8(+) T-cell responses, and viral sequence changes for 61 mother-child pairs from Durban, South Africa, who were monitored from birth. Slow progression was significantly associated with the mother or child possessing one of the protective HLA-B alleles, and more significantly so when the protective allele was not shared by mother and child (P = 0.007). Slow progressors tended to make CD8(+) T-cell responses to Gag epitopes presented by the protective HLA-B alleles, in contrast to progressors expressing the same alleles (P = 0.07; Fisher's exact test). Mothers expressing the protective alleles were significantly more likely to transmit escape variants within the Gag epitopes presented by those alleles than mothers not expressing those alleles (75% versus 21%; P = 0.001). Reversion of transmitted escape mutations was observed in all slow-progressing children whose mothers possessed protective HLA-B alleles. These data show that HLA class I alleles influence disease progression in pediatric as well as adult infection, both as a result of the CD8(+) T-cell responses generated in the child and through the transmission of low-fitness viruses by the mother.